ENHANCING CONTENT MARKETING PERFORMANCE THROUGH ARTIFICIAL INTELLIGENCE: A STRATEGIC FRAMEWORK - Chalirafi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study explores the emerging field of intelligent content marketing by examining how artificial intelligence (AI) can enhance the efficiency and effectiveness of content-driven marketing strategies. Drawing on a conceptual framework, the paper presents illustrative models that demonstrate the potential integration of AI technologies into marketing processes. The primary aim is to increase awareness of AI’s transformative role in content marketing and provide preliminary insights into future opportunities in the field. Although this is a conceptual investigation, the proposed models are intended for further empirical development and testing, particularly within social media and web-based environments. Future research will focus on the practical deployment and performance assessment of these models, contributing to the broader discourse on AI-enhanced marketing innovation.